Features of using fiber concrete for parapet-type restraining transport systems - Kochevykh, Maryna; Honchar, Olha; Anopko, Dmytro; Ivchenko, Oleksandra (КНУБА, 2025)
According to the Ministry of Reconstruction, 25,400 km of roads were destroyed as a result of hostilities in Ukraine, and according to experts, their reconstruction will take from 5 to 20 years, depending on the facility. Therefore, the issue of large-scale restoration and reconstruction of highways in Ukraine is relevant.
Keywords: fiber concrete; parapet transport; 666.982